ANALISIS LEKSIKAL ḤĀZAQ (חָזַק) DAN ’ĀMAṢ (אָמַץ) DALAM YOSUA 1:6-9: DIMENSI TEOLOGIS DALAM KEPEMIMPINAN DEUTERONOMISTIK - Inriyani; Putri Wahyuni Dewanto; Zhirene (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
This study aims to conduct a lexical analysis of two Hebrew verbs, ḥāzaq (חָזַק) and ’āmaṣ (אָמַץ), in Joshua 1:6–9 and to explore their theological dimensions within the framework of Deuteronomistic leadership. These verbs appear repeatedly in God’s command to Joshua to “be strong and courageous” as he assumes leadership of Israel after the death of Moses. The research employs a lexical analysis of the Hebrew text by examining the word forms, their basic meanings, and their usage within the Old Testament, particularly in the Deuteronomistic tradition. The findings indicate that ḥāzaq emphasizes strength, firmness, and resilience, highlighting the capacity to remain steadfast in the face of leadership challenges. In contrast, ’āmaṣ underscores inner courage, determination, and mental readiness to carry out the mission entrusted by God. The repetition of these verbs in Joshua 1:6–9 functions not only as a rhetorical reinforcement but also carries significant theological meaning, emphasizing that leadership in the Deuteronomistic perspective must be grounded in obedience to the Torah and trust in God’s presence. Therefore, the strength and courage commanded to Joshua are not merely physical or military attributes but primarily spiritual qualities rooted in a faithful relationship with God and adherence to His word. This study demonstrates that the Deuteronomistic concept of leadership integrates courage, obedience to divine law, and confidence in God’s guidance as the foundation for effective leadership of God’s people.